Managing Emotions in the Covid-19 Pandemic Support of Freight (Managing Emotions in Covid-19 Pandemic (Phenomenological Research towards Freight Forwarding Companies' Sales Support Employees in Semarang City) - Jasmine Yahya; Marwan Surya Perdhana (Budapest International Research and Critics University, 2022)
Emotional intelligence is the ability to conceive and manage our emotions and surroundings. It is a crucial ability that needs to be mastered in someone's life in order that they can deal with all kinds of situations that might occur in life patiently. During this Covid-19 pandemic, there have been many changes that have appeared in people's lives, which cause them to feel stressed and Burnout. This issue was also felt by some employees that experienced some changes in their work patterns when they had to implement a work-from-home system. The purpose of this research is to find out and analyze the strategies of the sales support employees in freight forwarding companies in managing their emotions during this pandemic and find out whether the WFH systems they have been doing during pandemics affect their performance. The outcomes that were obtained from research respondents shows that the pandemic and WFH system make them experience Burnout, while they also had to remain responsible for their work. Thus they were required to have various ways of dealing with Burnout. In addition, the WFH system also has an influence on employees' performance and time flexibility at work.